Negation Coding in Ga - Ollennu, Yvonne Akwele Amankwaa (My University, 2019)
The paper investigates negation coding in Ga, a Kwa language. Data analyzed in the paper was gathered from Ga students at the University of Education, Winneba, in addition to the researcher’s native intuition. According to Miestamo (2007) negation could be classified under two categories, standard and non-standard negation. It is noted that whichever type of negation is employed in a language, it will be done either morphologically or syntactically. The paper shows that both morphological and syntactic strategies are used for negation coding in Ga. The NP NP and copula types of sentences in Ga employ a syntactic strategy to code negation. On the other hand, SVO sentences are negated morphologically. The SVO type of sentences is negated morphologically via the tense or aspect of the verb type in Ga. The affixes used to negate the SVO sentences also depend on the type of verb used in the sentence.
Keywords: Negation coding; Ga; Kwa Language; SVO